1994
DOI: 10.3386/w4653
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital and the Birth of U.S. Biotechnology Enterprises

Abstract: We examine the relationship between the intellectual capital of scientists making frontier discoveries, the presence of great university bioscience programs, the presence of venture capital firms, other economic variables, and the founding of U.S. biotechnology enterprises during 1976-1989. Using a linked cross-section/time-series panel data set, we find that the timing and location of the birth of biotech enterprises is determined primarily by intellectual capital measures, particularly the local number of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
1,074
6
29

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 904 publications
(1,149 citation statements)
references
References 33 publications
40
1,074
6
29
Order By: Relevance
“…For example, in her study of innovation in tissue-engineered cartilage, Murray (2002) found that the commercialization of science into new medical treatments depends crucially on overlapping, but distinctive, scientific and technological networks at the institutional level. Connections to scientific networks, via key individuals who work at the interstices of such networks, provide 'knowledge spillover' effects that shape technological progress and influence firms' abilities to develop intellectual capital (Zucker et al 1998). This finding echoes earlier research on the important role of 'boundary spanners' who broker relationships across networks (e.g.…”
Section: Integrative Capabilitiessupporting
confidence: 64%
See 1 more Smart Citation
“…For example, in her study of innovation in tissue-engineered cartilage, Murray (2002) found that the commercialization of science into new medical treatments depends crucially on overlapping, but distinctive, scientific and technological networks at the institutional level. Connections to scientific networks, via key individuals who work at the interstices of such networks, provide 'knowledge spillover' effects that shape technological progress and influence firms' abilities to develop intellectual capital (Zucker et al 1998). This finding echoes earlier research on the important role of 'boundary spanners' who broker relationships across networks (e.g.…”
Section: Integrative Capabilitiessupporting
confidence: 64%
“…The importance of 'star scientists' has been noted elsewhere, but usually in terms of the role such individuals play in linking commercial activity to the knowledge base of academe (Zucker et al, 1998). Whilst this was important (and discussed above), here we use the term 'Figurehead' to highlight also their symbolic and motivational effects.…”
Section: Integrative Capabilitiesmentioning
confidence: 99%
“…Academic entrepreneurship research shows that working at the frontier gives academic scientists comparative advantage for identifying new breakthrough opportunities (Zucker et al, 1998;Franzoni and Lissoni, 2007). There is a large body of empirical research showing that researchers who are very active contributors to the pool of technological opportunities, tend to be particularly prominent in their respective fields.…”
Section: Excellence Of Academic Researchmentioning
confidence: 99%
“…Plutôt que la coexistence de deux univers de recherche bien différenciés, plusieurs auteurs y observent, au contraire, la constitution de réseaux agglomérés associant laboratoires publics et entreprises privées pour partager des équipements et des compétences (Zucker et al, 1998, Mc Kelvey, 1996. Le développement de spin off issues de la recherche fondamentale, et inversement, l'utilisation massive par les chercheurs de technologies et de services produits par les entreprises pour élaborer des connaissances scientifiques, attestent d'une évolution vers des formes de couplage étroits entre science et innovation.…”
unclassified